Imaginaries of the Pandemic in Chile: A Conceptual-Empirical Discussion - Vergara-Del Solar, A (John Wiley and Sons Inc, 2023)
This article aims to reconstruct the social imaginaries of Coronavirus disease 2019 (COVID-19) in Chile. We seek to understand how families interpret their experience confronting the pandemic by identifying four main aspects: (a) the COVID-19 pandemic, (b) working and learning, (c) health and (d) family life. Following Habermas distinction between lifeworld and social systems, we consider these issues as constituting the social imaginary of lifeworld, different but related to the imaginaries of social systems. The qualitative empirical data was gathered through a sample of 38 families interviewed online between September 2020 and January 2021 in four Chilean cities: Iquique, Valparaíso, Santiago and Concepción. Other complementary sources of information are multimodal ethnography (digital diaries), press articles and state reports. © 2022 Society for Latin American Studies.